Celebrating Achievements as Digital Rituals among Indonesian Youth on Social Media - Sujibto, B.J.; Natiqoh, Malikatun; Nuzulanisa, Kafhaya; Widodo, Saras Wati (UI Scholars Hub, 2025)
Youth and social media are increasingly intertwined, as their socio-cultural trajectories accelerate digital connectedness and intensify the contestation of diverse identities. Posting on social media has thus become a ritualized practice. This article explores how Indonesian university students construct identities by sharing achievement stories and success narratives on Instagram. Using qualitative data, it examines the experiences of students who have excelled in academic competitions. The study identifies two key typologies behind such posts. Firstly, personal determinism, aimed at self- reward and self-branding. Secondly, social motivation, focused on inspiring peers and building supportive networks to achieve academic success. These typologies reflect a shift in ritual practices, from sacred, magical traditions emphasized in classical sociology and anthropology, to everyday, mediated acts as conceptualized in Goffman’s sociology. Such digital rituals represent a broader transformation of daily practices into a digital culture.